Ischemic Complications after Liver Transplantation - Ingraham, Christopher R.; Montenovo, Martin I. (Digestive Disease Interventions, 2018)
Despite major advances in the field of liver transplantation over the past few decades with both increased graft and patient survival, biliary complications still occur in many patients after liver transplantation. Complications can range from a biliary leak or biloma to strictures most commonly involving the surgical anastomosis, or elsewhere in the biliary tree. Etiologies of these complications include surgical technique, rejection, complications secondary to infection, and vascular complications causing ischemia of the bile ducts. Biliary complications, particularly biliary ischemia, can cause significant morbidity to the patient, and may require multiple endoscopic, endovascular, or percutaneous therapies for successful treatment, or even retransplantation in severe cases. This review will provide an overview of common biliary complications with a focus on biliary ischemia.
Keywords: biliary ischemia; liver transplantation; biliary stricture; percutaneous biliary drainage; hepatic artery stenosis; hepatic artery thrombosis